2013
DOI: 10.1080/02508060.2013.817042
|View full text |Cite
|
Sign up to set email alerts
|

Constraints and opportunities for groundwater irrigation arising from hydrologic shifts in the Iullemmeden Basin, south-western Niger

Abstract: Land-use-change-induced increases in shallow groundwater levels across parts of the Sahel in recent years have coincided with expanded use of groundwater for irrigation. This study was conducted to assess the potential linkages and livelihood implications based on a field survey of nine villages building on previous hydrological studies. The results show that irrigators lack effective means of production and mostly rely on manual methods. Borehole usage is more profitable and reliable than shallower wells. Ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…Further, they indicated that these barriers outweighed irrigation issues, although some are linked. This finding is consistent with Torou et al (2013), who reported that lack of access to seeds and fertilizer are problems affecting the productivity of groundwater irrigation schemes in Niger. The present findings suggest that lack of finance could be a root cause of many of these barriers.…”
Section: Access To Information and Knowledge On Crop Productionsupporting
confidence: 82%
“…Further, they indicated that these barriers outweighed irrigation issues, although some are linked. This finding is consistent with Torou et al (2013), who reported that lack of access to seeds and fertilizer are problems affecting the productivity of groundwater irrigation schemes in Niger. The present findings suggest that lack of finance could be a root cause of many of these barriers.…”
Section: Access To Information and Knowledge On Crop Productionsupporting
confidence: 82%
“…La promotion de la petite irrigation privée à partir des eaux souterraines peu profondes est économiquement envisageable car les coûts des ouvrages de captage et des moyens d'exhaure sont réduits. Depuis 1990, les PIP suscitent un engouement certain dans le pays (Torou et al, 2013). Il s'agit de stimuler cette dynamique à travers des politiques appropriées ; l'adoption en 2015 de la SPIN s'inscrit bien dans cette logique.…”
Section: Resultsunclassified
“…The transformation of the pastoral zone into a contested landscape will continue unabated, especially due to the agreed usefulness of irrigated gardening in supporting livelihoods facing climate variability in Niger. Yet, under what conditions should such gardens and their respective enclosures be established (see also Torou et al, 2013)? Enclosures redefine the political and social order of a system with new rules and institutions on how the environment is accessed and managed (Schmidt and Pearson, 2016), who benefits, and who is able to decide on boundaries.…”
Section: Discussion: Gardening As Divergent Adaptation In the Pastoramentioning
confidence: 99%